Trade Policy Uncertainty, Offshoring, and the Environment: Evidence from US Manufacturing Establishments - Jaerim Choi; Jay Hyun; Gueyon Kim; Ziho Park (Institute of Labor Economics (IZA), 2023)
We study long-run environmental impacts of trade liberalization on US manufacturing by exploiting a plausibly exogenous reduction in US trade policy uncertainty: the conferral of Permanent Normal Trade Relations (PNTR) to China. Using detailed data on establishment-level pollution emissions and business characteristics - including trade activities and global subsidiary information - from 1997 to 2017, we show that establishments reduce toxic emissions in response to a reduction in trade policy uncertainty. Emission abatement is mainly driven by a decline in pollution emission intensity, and not by establishment exits or a reduction in production scale. Emission reduction is more pronounced for (i) establishments with foreign sourcing networks and (ii) those under more stringent environmental regulations. We provide further evidence that supports the pollution haven hypothesis whereby offshoring is central to the mechanism - US manufacturers begin to source from abroad and establish more subsidiaries in China after PNTR, especially those that emit pollutants heavily.
Keywords: Q53; Q56; F14; F18; F23; 330; pollution haven hypothesis; toxics release inventory; pollution emissions; trade and environment; trade policy uncertainty; offshoring; particulate matter; PNTR